PERBEDAAN UKURAN PARTIKEL TERHADAP KUALITAS BRIKET ARANG DAUN PISANG KERING - Alfajriandi Alfajriandi; Faizah Hamzah; Farida Hanum Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Dry banana leaves contain beneficial compounds lignin and cellulose which is quite high and has not been utilized optimally. Therefore, the study aims to take advantage of dry banana leaves as the main material for the manufacturing of charcoal briquettes and charcoal briquettes obtain formulations are of good quality. The study was conducted experimentally using Complete Random Design (CRD) with 6 treatments and 3 replications and continued with Duncan’s New Multiple Range Test (DNMRT) at level 5%. The treatmentsin the research including P0 (charcoal powder dry banana leaveswithout sieve), P1 (charcoal powder dry banana leaves20 mesh), P2 (charcoal powder dry banana leaves40 mesh), P3 (charcoal powder dry banana leaves60 mesh), P4 (charcoal powder dry banana leaves80 mesh), and P5 (charcoal powder dry banana leaves100 mesh). The result of analysis of variance showed that the particle size charcoal dry banana leaves significant effect on ash content, density, calorific value and fueled power. Selected treatment wasP3 (charcoal powder dry banana leaves 60 mesh) which has a water content 6.80%, ash content of 29.86%, a density of 0.38 g/cm3, 4646 calorific value cal/g, and fueled power 0.0016 g/sec. Keywords: briquettes, dry banana leaves, particle size.